INVESTIGATION OF CONSTANT ATTENTION SKILLS OF HEARING IMPAIRED INDIVIDUALS WHO DO AND DON’T DO SPORTS IN TERMS OF SOME VARIABLES - Aydin, Elif; Baş, Mustafa; Ölçücü, Burçin; Bülbül, Alpay (Acta Scientiae et Intellectus, 2024)
The purpose of this research; is the study of constant attention skills in hearing impaired individuals who do and do not play sports in terms of some variables. A total of 101 hearing-impaired people living in Trabzon, 43 individuals aged 12-17 who regularly sport and 58 individuals who do not play sports participated in the research. The personal information form developed by the researcher in the study and the Burdon Attention Test were used to determine the attentiveness of the participants. Kruskal Wallis H test and Mann Whitney U tests were used in the statistical analysis of the data obtained in the study. Statistically significant level of significance was determined as p <0,05.